Connecting Classrooms and Communities Across Continents to Strengthen Health Promotion Pedagogy: Development of the Transnational Education and Community Health Collaborative (TEaCH CoLab). (December 2022) - Carroll, Paula; Early, Jody O.; Murphy, Niamh; O'Connor, Jenny; Barry, Mairead; Eagan-Torkko, Megan; O'Connor, Robert; Richardson, Noel; Stone, Andrea
Tackling complex twenty-first century global health challenges requires crossdisciplinary collaborations that extend beyond physical classrooms and across continents. The Transdisciplinary Education and Community Health Collaboratory (TEaCH CoLab) is a global teaching co-op established by health promotion and humanities faculty at three universities (Waterford Institute of Technology and the Institute of Technology, Carlow in Ireland, and the University of Washington, Bothell in the U.S.). The primary goals of TEaCH CoLab are to enhance global learning and problem-solving among the next generation of community and public health practitioners, to improve public health teaching (with a focus on digital pedagogy), and to increase empathy and community-connectedness. In this descriptive article, we present our program model and lessons learned from the first three years of collaboration to provide insights into how such capacity-building projects are established and sustained over time and across diverse geographical, cultural and temporal landscapes. Collaboration happens primarily online through academic and community partnerships, collaborative online learning, and pedagogy discussion and development. Students get to engage with course content and experiential learning that is part of a shared, global curriculum which emphasizes social justice, health equity, cultural humility and anti-racism, and advocacy. Our "lessons for the field" are collective, practice-based reflections by members of TEaCH CoLab based on their experiences and their involvement in development and facilitation. Our model for learning may help other health promotion scholars and practitioners develop meaningful global learning experiences that strengthen the interconnectedness of praxis, pedagogy, and communities.